Hi,
This is quite a basic query but I am having difficulty figuring out the following and would like some assistance.
(x+3)-(x+1)
= x+3-x-1
=2
I don't understand how we end up with = x+3-x-1
Could some please explain the steps taken to get here?
Many thanks
I use to get so confused with expressions like this but its pretty simple actually
if you see -+ sign in between the two you should know you have to multiply them with the numbers inside the brackets.
(x+3) -(x+1)
(x+3) -1(x+1) there is a imaginary 1 after the negative value if you can see it like that.
x+3 -x-1
x+3-x-1
x-x=0
3-1=2